Copenhagen ; [videorecording (DVD)] Fleming : the man who would be Bond. - Craig, Daniel; Rea, Stephen; Cooper, Dominic, 1978- (Bbc Us / Canada, 2015)
The adaptation of Michael Frayn's celebrated stage play about a meeting between physicists and the story of the character that was the inspiration for James Bond.